PENGEMBANGAN MODUL MENULIS TEGAK BERSAMBUNG BERBASIS SENSORI MOTORIK DALAM PEMBELAJARAN MENULIS PERMULAAN SISWA KELAS II SEKOLAH DASAR - Ayu Koernia Malyk; Fahrurrozi; Edwita (STKIP Subang, 2022)
Cursive writing is an essential writing skill that must be mastered by second grade elementary school students. However, the use of teaching materials in schools is still limited. The average students learning outcomes also have not achieved maximum result. This research and development aims to produce a product in the form of a cursive writing module based on sensory motor in beginning writing learning grade II elementary school. The development of this cursive writing module uses the Research and Development (RnD) method with the Borg and Gall model through 7 stages. Data collection techniques consisted of observation, interviews, questionnaires, and tests. This product has gone through a validation test by getting a percentage of 93.75% by media expert in the